Āra nodarbības dabaszinātņu mācību jomas satura apguvei bērniem pirmsskolas izglītības otrajā posmā - Ļufte, Sintija (Latvijas Universitāte, 2023)
Kvalifikācijas darbu “Āra nodarbības dabaszinātņu mācību jomas satura apguvei bērniem pirmsskolas izglītības otrajā posmā” ir izstrādājusi Latvijas universitātes, Pedagoģijas, psiholoģijas un mākslas fakultātes, nepilna laika 1.līmeņa profesionālās studiju programmas “Pirmsskolas izglītības skolotājs” studente Sintija Ļufte. Darba vadītājas Ilzes Miķelsones vadībā. Darba pētāmais jautājums: kā organizēt āra nodarbības dabas zinātņu mācību jomas satura apguvei bērniem pirmsskolas izglītības otrajā posmā? Kvalifikācijas darba mērķis ir izzināt āra nodarbību pielietojumu dabas zinātņu mācību jomas satura apguvei bērniem pirmsskolas izglītības otrajā posmā. Darba ietvaros tika izpētīta un izanalizēta zinātniskā literatūra par 3-4 gadus vecu bērnu darbošanos āra vidē, izstrādāti paņēmieni, kas ļauj izpētīt bērnu ieinteresētību darboties rotaļnodarbībā āra vidē. Pētījuma galvenie secinājumi ir, ka bērni, darbojoties rotaļnodarbībā āra vidē, ir ieinteresēti dabas procesu izzināšanā, bērni ir aktīvi un labprāt iesaistās rotaļnodarbībā. Atslēgas vārdi: rotaļnodarbība, āra vide, dabaszinātņu joma, pirmsskolas izglītība, skolotāja atbalsts, rotaļdarbība āra vidē. Darbs satur: 23. literatūras avotus, no tiem 8 svešvalodās (4 angļu valodā, 1 krievu valodā, 3 vācu valodā) 38 lapas, 7 attēlus, 9 tabulas.

The qualification work "Outdoor lessons for learning the content of the field of natural sciences for children in the second stage of preschool education" was developed by Sintija Įfte, a student of the part-time level 1 professional study program "Teacher of Preschool Education" at the Faculty of Pedagogy, Psychology and Art, University of Latvia. Under the leadership of the supervisor Ilze Miķelsone. The research question: how to organize outdoor lessons for learning the content of natural sciences children in the second stage of preschool education? The purpose of the qualification work is to find out the application of outdoor lessons for learning the content of the field of natural sciences for children in the second stage of preschool education. Within the scope of the work, the scientific literature on the activity of 3-4-year-old children in the outdoor environment was researched and analyzed, and techniques were developed that allowed studying children's interest in playing in an outdoor environment. The main conclusions of the study are that children are interested in learning about natural processes while playing in the outdoor environment, and children are active and willingly participate in the play. The qualification work "Outdoor lessons for learning the content of the field of natural sciences for children in the second stage of preschool education" was developed by Sintija Įfte, a student of the part-time level 1 professional study program "Teacher of Preschool Education" at the Faculty of Pedagogy, Psychology and Art, University of Latvia. Under the leadership of the supervisor Ilze Miķelsone. The research question: how to organize outdoor lessons for learning the content of natural sciences children in the second stage of preschool education? The purpose of the qualification work is to find out the application of outdoor lessons for learning the content of the field of natural sciences for children in the second stage of preschool education. Within the scope of the work, the scientific literature on the activity of 3-4-year-old children in the outdoor environment was researched and analyzed, and techniques were developed that allowed studying children's interest in playing in an outdoor environment. The study’s main conclusions are that children are interested in learning about natural processes while playing in the outdoor environment, and children are active and willingly participate in the play. Keywords: play lesson, outdoor environment, the field of natural sciences, Teachers’ support, preschool education, outdoor activities. The work contains 23 literary sources, of which 8 are in foreign languages (4 in English, 1 in Russian, 3 in German), 38 pages, 7 pictures, and 9 tables.
Outdoor lessons for learning the content of the field of natural sciences for children in the second stage of preschool education
Keywords: Izglītības zinātnes; rotaļnodarbība; āra vide; dabaszinātņu joma; pirmsskolas izglītība; skolotāja atbalsts